Pelatihan Penelitian Tindakan Kelas Untuk Pengembangan Profesi Guru Era Kurilulum Merdeka Bagi Guru SMK Negeri 5 Kota Bengkulu - Sudarwan Danim; Rahmat Ramelan Setyabudi (Universitas PGRI Palembang, 2022)
The aims of this training is to implement one of the function of higher education, in the form of writing class action research (CAR) for professional development of teachers in the Freedom Curriculum era, at SMK Negeri 5 Bengkulu City. The training methods used are: (1) detecting teachers' initial understanding of the implementation of classroom action research (CAR) in the framework of professional development in the Merdeka Curriculum era, (2) tutorials, namely providing opportunities for trainees to discuss; (3) lectures, in which the trainer explains to the trainees what and how to prepare CAR; and (4) writing practice, where training participants are invited to write CAR proposals together. The number of training participants was 40 people. The results of the evaluation of the implementation of CAR training showed that the participants had an initial understanding of the implementation of CAR in the framework of professional development in the Freedom Curriculum era. The trainees took good opportunities to discuss and complete tasks during the training. Even so, when participants were asked to prepare CAR proposals, they found errors in substance, language, and procedures that had to be followed.